2023
DOI: 10.3390/nu15112480
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Inhalation of Peppermint Essential Oil Improves Exercise Performance in Endurance-Trained Rats

Abstract: Peppermint essential oil, being natural and safe, with antioxidant and anti-inflammatory properties, has long been a research interest in relieving fatigue and improving exercise performance. However, the related studies report controversial results, and the mechanisms remain unclear. Here we found that inhalation of peppermint essential oil significantly extended the exhaustion time in rats subjected to 2-week weight-bearing swimming training. Sprague-Dawley rats were subjected to a 2-week weight-loaded force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The combination 0.5 mix and mix Nano emulsions was superior to the individual ones at different time intervals which proves its anti-oxidant effect when combined together during burn healing, suggesting that they can help in preventing the production and scavenging of ROS. Prolonged inflammatory response is a serious issue in patient with severe burn injuries and can lead to systemic complications [34]. It has been shown that lavender [35]., frankincense [36] and peppermint [37] oils are significantly able to reduce inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The combination 0.5 mix and mix Nano emulsions was superior to the individual ones at different time intervals which proves its anti-oxidant effect when combined together during burn healing, suggesting that they can help in preventing the production and scavenging of ROS. Prolonged inflammatory response is a serious issue in patient with severe burn injuries and can lead to systemic complications [34]. It has been shown that lavender [35]., frankincense [36] and peppermint [37] oils are significantly able to reduce inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Plant essential oils can purify the air, and their pleasant aroma can relieve fatigue [ 33 ] and improve sleep [ 34 ]. They can also be anti-inflammatory [ 35 ], antioxidant, and bactericidal, with medicinal values [ 36 ].…”
Section: Preservation Materials Containing Mixed Extractsmentioning
confidence: 99%
“…It is a general belief that physical exercise challenges the body's homeostasis and elicits a measurable physiological response. Notably, there is a substantial increase in muscle metabolism, which triggers an increase in the blood circulatory system and gas exchange [ 5 ]. For this, in addition to a formal training program, there are other strategies to prevent or delay fatigue, such as supplements and aromatherapy [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to Pournemati et al [ 6 ], the improvement in performance through PEO may be related to its action on cell membranes by regulating the flow of Ca 2+ (Calcium). PEO, with its active ingredients, is believed to reduce oxidative stress and inflammation induced by exercise and thus relieve exercise-induced fatigue and improve exercise performance [ 4 , 5 ]. Numerous types of essential oils exist with varying compositions and effects.…”
Section: Introductionmentioning
confidence: 99%